Modeling Approach to Optimizing Dose Regimen of Vancomycin for Chinese Pediatric Patients with Gram-Positive Bacterial Infections - Shen, Kai; Fan, Yaxin; Yang, Minjie; Chen, Yuancheng; Tao, Jinhao; Lu, Guoping; Zhang, Hong; Huang, Qiwei; Zhang, Jing (Frontiers in Pharmacology, 2021)
The aim of this study was to establish the population pharmacokinetics (PK) model of Vancomycin for Chinese pediatric patients which can extrapolate to whole age periods by bridging the published adult population PK model and the established pediatric population PK model. The final consolidated population PK model was used to explore the correlation of pharmacokinetics/pharmacodynamics (PK/PD) indices and efficacy of vancomycin and to provide evidence for the optimized regimen of vancomycin in Chinese pediatric patients with gram-positive bacterial infection. 108 pediatric patients with gram-positive infections from 2 pediatric hospitals in China in the first period of the prospective multi-center vancomycin clinical observational study were enrolled to establish the population PK model. A one-compartment population PK model was established and validated. The correlation between vancomycin PK/PD indices(trough concentration [Cmin], peak concentration [Cmax], 0-24 hour area under the curve [AUC0-24] and the area under the curve to minimum inhibitory concentration ratio [AUC0-24/MIC]) and the overall clinical outcomes (clinical efficacy and microbiological efficacy) in Chinese pediatric patients were evaluated. There is no significant correlation between PK/PD indices and clinical efficacy or microbiological efficacy. Considering the high clinical effective rate (>90%) and median AUC0-24/MIC values of 200 to 300, Chinese pediatric patients with gram-positive bacterial infection may be suitable for lower AUC0-24/MIC target value compared to the target value of 400 to 600 recommended by IDSA guideline. Different optimal dose regimen of vancomycin for Chinese pediatric patients should be considered. Further evaluation in more prospective studies will be needed.